PENGEMBANGAN SISTEM INFORMASI BERBASIS ANDROID “VITA NUTRI HEALTH” PADA REMAJA OVERWEIGHT - Chyntia Anggraini Putri (Program Studi Informatika Medis Universitas Muhammadiyah Muara Bungo, 2025)
The current rapid development of technology, particularly in the field of information technology, aims to assist human activities. This is evident from the use of computers, mobile applications, various supporting applications, and the internet as a bridge for information exchange. According to the WHO, in 2022, more than 390 million children and adolescents aged 5-19 were overweight. The objective of this research was to develop the Android-based information system VitaNutriHealth as an educational tool for adolescents at high school in Malang. The Vita Nutri Health application was proven to significantly influence students' knowledge, attitudes, and eating behaviors. This study used a qualitative and quantitative approach. Based on statistical tests, the data on students' knowledge, attitudes, and food consumption behavior showed a significant change (p-value < 0.05) after the intervention with this application. Overall, the application was proven to be an effective nutritional education tool for overweight adolescents.